Exploratory Study for the development of new methodologies for antibiotics determination in water samples - Godinho, Bruno M. C. (2008)
It is nowadays well established that antibiotics are constantly released into the environment as a consequence of their broad use in human and animal therapy. The presence of these substances in superficial, underground, and residual waters, has been detected by several authors. Resistant bacterial strains and toxicity risks are the major concerning impact on the environment which demands quality control of the waters. Thus, the development of new methodologies for environmental antibiotic determination is an important issue. The suitability of a Solid Phase extraction technique using a C-18 reversed phase packed material and several elution solvents was tested for the detection of Tetracycline (TC), Chloramphenicol (CPA), and Streptomycin (STP) in standard water samples. The chromatographic separation was held in High-Pressure Liquid Chromatography equipment with a diode array detector, using a C-18 reversed-phase column (30cm x 3.9mm d.i., 5μm particle size). The specific absorption wavelength for each antibiotic was monitored: 357, 277, and 257nm for TC, CPA, and STP. The elution solvent was a determinant for the extraction step, as we achieve 77,1% recovery for TC and 15,3% for CPA; no recovery was achieved for STP. Therefore, a method of analysis for the TC and CPA was established, however, a separate method of analysis is suggested for the analysis of STP, due to its high polar behavior.